Analysis of psychological and academic factors related to anxiety about entering the workforce among final semester students Payung Negeri Aceh Darussalam Health Sciences Institute 2025 - Rahmiati Tagore Putri; Saipullah Saipullah (Science Midwifery, 2026)
Anxiety about entering the workforce is an emotional condition characterized by feelings of tension, worry, and uncertainty about one's ability to cope with the demands and transition to a new work environment. The purpose of this study is to examine the intellectual and psychological aspects of final-year STIKes Payung Negeri Aceh Darussalam students' worry about starting a career in 2025. The investigation was carried out during October 1–3, 2025, using a cross-sectional study design and a quantitative analytical approach. The Slovin algorithm and simple random sampling were used to choose 60 responders from the 152 final-year students that made up the study population. Data were collected through interviews using a structured questionnaire and analyzed using SPSS with the Chi-Square test (p < 0.05). The results of the study show a significant relationship between self-confidence (p=0.045), social support (p=0.033), work experience (p=0.006), work readiness (p=0.021), and sources of information (p=0.006) with anxiety about entering the workforce. These results confirm that anxiety is more influenced by psychological factors and personal experiences than academic achievement alone. Therefore, universities need to develop career development programs, soft skills training, counseling, and internships to improve students' mental readiness for the world of work.